1994
DOI: 10.1016/s0006-3495(94)80957-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the profile structure of the sarcoplasmic reticulum membrane induced by phosphorylation of the Ca2+ ATPase enzyme in the presence of terbium: a time-resolved x-ray diffraction study

Abstract: The design of the time-resolved x-ray diffraction experiments reported in this and an accompanying paper was based on direct measurements of enzyme phosphorylation using [gamma-32P]ATP that were employed to determine the extent to which the lanthanides La3+ and Tb3+ activate phosphorylation of the Ca2+ATPase and their effect on the kinetics of phosphoenzyme formation and decay. We found that, under the conditions of our experiments, the two lanthanides are capable of activating phosphorylation of the ATPase, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…The methods and procedures used for the preparation of the hydrated, oriented multilayer specimens of isolated SR membranes, the collection of their lamellar x-ray diffraction data, and initial diffraction data reduction are described in an accompanying paper (Asturias et al, 1994), and will not be presented here. The result of the first phase of data reduction were sets of three background scattering-corrected, lamellar intensity functions I(Z*, Eedge), and I(z*, Eedge+a) per stable specimen, where Eedge represents the x-ray energy corresponding to the terbium LIM absorption edge (7506 eV), and A = +100 eV.…”
Section: Methods and Data Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The methods and procedures used for the preparation of the hydrated, oriented multilayer specimens of isolated SR membranes, the collection of their lamellar x-ray diffraction data, and initial diffraction data reduction are described in an accompanying paper (Asturias et al, 1994), and will not be presented here. The result of the first phase of data reduction were sets of three background scattering-corrected, lamellar intensity functions I(Z*, Eedge), and I(z*, Eedge+a) per stable specimen, where Eedge represents the x-ray energy corresponding to the terbium LIM absorption edge (7506 eV), and A = +100 eV.…”
Section: Methods and Data Analysismentioning
confidence: 99%
“…The result of the first phase of data reduction were sets of three background scattering-corrected, lamellar intensity functions I(Z*, Eedge), and I(z*, Eedge+a) per stable specimen, where Eedge represents the x-ray energy corresponding to the terbium LIM absorption edge (7506 eV), and A = +100 eV. For the time-resolved, nonresonance x-ray diffraction study, only the edge-energy lamellar intensity functions I,(z*, Eedge) were analyzed further to derive the relative electron density profile for the multilayer unit cell containing two apposed profiles of the SR membrane, and the nonresonant changes in the unit cell and single SR membrane profile upon flash photolysis of caged ATP and subsequent protein phosphorylation in the multilayer specimens were determined (Asturias et al, 1994).…”
Section: Methods and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that Dy 3+ inhibits this enzyme much more than other lanthanide ions (Van der Laarse et al, 1995). La 3+ and Tb 3+ trigger phosphorylation of Ca 2+ -ATPase and increase the half-life of the phosphorylated enzyme (Asturias et al, 1994). Lanthanum ions can inhibit Mg 2+ -ATPases and choline esterases and activate kinase C (Wadkins et al, 1998).…”
Section: Cytophysiological Effects Of Lanthanidesmentioning
confidence: 99%
“…This may be explained by assuming that the E 1~P form of the enzyme is the dominant intermediate during the steady state. La 3+ and Tb 3+ also activate the phosphorylation of Ca 2+ -ATPase (Asturias et al, 1994b) and the Tb 3+ induced phosphoenzyme formation was accompanied by decrease in electron density in the outer phospholipid monolayer and an increase in the inner phospholipid monolayer. These changes are qualitatively similar to those observed in the presence of Ca 2+ (Herbette et al, 1985;Blasie et al, 1990) but smaller in magnitude due perhaps to the lower steady state concentrations of E~P found in the presence of Tb 3+ (Asturias et al, 1994b).…”
Section: Lamellar X-ray and Neutron Diffraction Analysis Of The Profimentioning
confidence: 95%